Narcissistic traits and compassion: Embracing oneself while devoiding others - Freund, Vanessa Lea; Peeters, Frenk; Meesters, Cor; Geschwind, Nicole; Lemmens, Lotte H. J. M.; Bernstein, David P.; Lobbestael, Jill (Frontiers in Psychology, 2022)
Grandiose narcissistic traits refer to exploitative and arrogant attitudes, while vulnerable narcissistic traits entail hypersensitivity to judgement and low self-esteem. Little is known about how individuals with narcissistic traits can improve their attitudes towards themselves and others. The current research puts self- and other-compassion forward as possible targets to alleviate some of narcissism’s destructive patterns. Generally, self-compassion (SC) has previously been associated with beneficial effects on psychological well-being, while other-compassion (OC) is advantageous for interpersonal relationships. The present study explored the relationship between narcissistic traits and the efficacy of experimental compassion inductions. Student and community participants (N=230, Mage=27.41, 65.2% female) completed grandiose and vulnerable narcissistic trait-, SC and OC state- questionnaires, and either an SC or OC induction. It was expected that individuals with higher narcissistic traits (particularly grandiose traits) would benefit from the inductions and show higher SC after, but would have greater difficulty showing meaningful increases in OC (especially OC directed at the general population). Results indicated that individual differences in grandiose and vulnerable narcissistic traits related to the magnitude of improvements following the inductions: the theorised lack of SC in individuals with vulnerable oversensitivity to judgement traits seems possible to be counteracted through different types of compassion exercises. Moreover, higher grandiose exploitativeness-entitlement, and global vulnerable narcissistic traits related to less increases in compassion for others. However, directly inducing OC in individuals with these traits was linked to greater OC improvements compared to improvements after inducing SC. Overall, the present findings suggest that self-compassionate behaviour can be improved in individuals with high oversensitivity and that other-compassionate behaviour could potentially be increased if, specifically, other-compassion exercises are utilised when higher levels of certain narcissistic traits are present.